ATOPIC DERMATITIS IN CHILDREN - Harfman Mihajlovic, Katarina (Acta medicae Medianae, 2023)
Atopic dermatitis represents a non-infectious, multifactorial inflammatory and chronic dermatosis. Pruritus is the main symptom. The pathophysiology of atopic dermatitis is very complex and includes genetic disorders, a defect in the epidermal barrier, an altered immune response and a disruption of the skin’s microbial balance, all of which damage the epidermis, causing itchy skin lesions. The prevalence varies, but it is generally present in 30% of children, and 85% of cases manifest before the age of 5. The triad of atopic diseases consists of atopic dermatitis, allergic rhinitis and asthma. A retrospective analysis of the documentation of the children who were treated at the Pediatric Clinic of the University Clinical Center Niš from 2018 to 2019 focused on anamnestic data, clinical manifestations, and laboratory parameters obtained from the medical records of the subjects. The total number of examined children was 40, among them, 21 were male and 19 female. They were divided into 3 age groups, from 2 months to 7 years. Anamnestic data indicate a connection between AD and other disorders of atopic diseases, allergic rhinitis, asthma, respiratory infections, and milk allergies.